2015
DOI: 10.1177/1934578x1501000239
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Constituents from the Leaves, Fruits (Berries), Stems and Roots of Solanum xanthocarpum from Nepal

Abstract: The essential oils from the leaves, fruits, roots, and stems of Solanum xanthocarpum, growing wild in Nepal, have been obtained and analyzed by gas chromatography-mass spectrometry. The fruit volatiles were dominated by benzyl benzoate (21.7%) and (E,E)-geranyl linalool (12.6%); heptacosane (20.0%) was the major component of the leaf oil; the stem oil was dominated by palmitic acid (28.9%), heptacosane (12.8%) and linoleic acid (10.1%); while solavetivone (22.9%), palmitic acid (21.0%), and linoleic acid (8.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The phenol has been reported to have antifungal, antibacterial, antioxidant, anti-Inflammatory and antimalarial activity [50][51]. E-14-Hexadecenal and E-15-Heptadecenal are aldehydes which have been previously reported in solanum species such as S. xanthocarpum [52], and have good antibacterial and antioxidant activity.…”
Section: Gc-ms Results Of Solanum Incanummentioning
confidence: 91%
“…The phenol has been reported to have antifungal, antibacterial, antioxidant, anti-Inflammatory and antimalarial activity [50][51]. E-14-Hexadecenal and E-15-Heptadecenal are aldehydes which have been previously reported in solanum species such as S. xanthocarpum [52], and have good antibacterial and antioxidant activity.…”
Section: Gc-ms Results Of Solanum Incanummentioning
confidence: 91%
“…Benzyl benzoate is the main constituent of Cananga odorata (Lam.) Hook & Thomson (ylang-ylang) [29] and Aniba hostmanniana (Nees) Mez (29.3%; GC-MS) essential oils [30], of volatile oils isolated from Solanum xanthocarpum Schrad & Wendl fruit (21.7%; GC-MS) [31], and from Senna hirsuta (L.), Irwin & Barneby (24.7%; GC-MS) [32]. Benzyl benzoate is a natural product known to be found in the essential oils of rosewood ( Dalbergia sissoo L.), cinnamon ( Cinnamomun verum Presl) and in balsam of Peru ( Myroxylon balsamum (L.) Harms).…”
Section: Resultsmentioning
confidence: 99%
“…S. xanthocarpum is an important source of many pharmacologically and medicinally useful alkaloids. Recent GC-MS analysis showed that several essential oils from leaves, fruits, roots, and stems of S. xanthocarpum were responsible for larvicidal activity [ 111 ]. Six important phytosteroids (1, 2-benzenedicarboxylic acid, dibutyl phthalate, phytol, lauric acid, 3,7,11,15-tetramethyl-2-hexadec, and 7-hexadecenal) with larvicidal activity against early 3rd instar larvae of the Cx.…”
Section: Solanaceae Familymentioning
confidence: 99%